The academic publication of famous memoirs of general A. I. Denikin - V. S. Izmozik (Омский научный вестник: Серия "Общество. История. Современность")
The article tells about the history of preparation for publication of the first in Russia academic publication of «Essays on the Russian Troubles» by General A. I. Denikin. The author draws attention to the source database of comments based on unpublished archival material, as well as to the high professional level of the specialists who participated in the preparation of the peer-reviewed edition of Essays on Russian Troubles. According to the author of the article, the importance of this publication as a source on the history of the revolution and the Civil War cannot be overestimated